{shorts}: An R Package for Modeling Short Sprints - Mladen Jovanović; Jason Vescovi (International Universities Strength and Conditioning Association, 2022)
Short sprint performance is one of the most distinguishable and admired physical traits in sports. Short sprints have been modeled using the mono-exponential equation that involves two parameters: (1) maximum sprinting speed (MSS) and (2) relative acceleration (TAU). The most common methods to assess short sprint performance are with a radar gun or timing gates. In this paper, we: 1) provide the shorts package that can model sprint timing data from these two sources; 2) discuss potential issues with assessing sprint time (synchronization and flying start, respectively); and 3) provide model definitions within the shorts package to help alleviate errors within the subsequent parameter outcomes.